PENGARUH PENAMBAHAN PASIR LAUT UNTUK MENINGKATKAN KUALITAS DAYA CERNA PAKAN TERHADAP AYAM BROILER - Cheppy Wati; Farid Maulana; Susan C. Labatar (Politeknik Pembangunan Pertanian Manokwari, 2016)
This study aimed to: 1). know the percentage of sea sand that gives the best effect on the quality of the digestibility in broiler; 2). to determine the impact of sea sand on the health of the digestive tract of broilers. The research was conducted during the first maintenance period (2 months) from September 11 until October 22, 2015, location of research conducted in broiler coop lecturer Extension Livestock Agricultural High School Manokwari, Manokwari STPP Complex, SPMA road Reremi Manokwari. This study was an experimental, the design of the study is a single factor with the addition of sea sand cattle feed, single factor in this research was the sea sand with different percentages comprised 5 treatments namely: p0 = without the addition of sea sand, p1 = addition of sea sand with a concentration of 100: 1 (100% total feed demand, added 1% sand sea ofthe total feed requirement), p2 = addition of sea sand with a concentration of 100: 2 (100% total feed requirement, added 2% sand sea of the total feed requirements) , p3 = addition of sea sand with a concentration of 100: 3 (100% total feed requirement, added 3% sand sea of the total feed requirement), p4 = addition of sea sand with a concentration of 100: 4 (100% total feed requirement, added 4% sand of the total feed requirements). The results showed that the addition of sea sand in the feed of broilers can improve the quality of the digestibility of feed to broilers (Gallus sp.) The addition of sea sand in the feed of broilers increase body weight gain, feed conversion and mortality in broilers, reduces mortality in broiler, The addition of sea sand in broiler feed of the best in the feed of 2% at treatment p2.